If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + -1 = 6m + 7 Reorder the terms: -1 + 4m = 6m + 7 Reorder the terms: -1 + 4m = 7 + 6m Solving -1 + 4m = 7 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. -1 + 4m + -6m = 7 + 6m + -6m Combine like terms: 4m + -6m = -2m -1 + -2m = 7 + 6m + -6m Combine like terms: 6m + -6m = 0 -1 + -2m = 7 + 0 -1 + -2m = 7 Add '1' to each side of the equation. -1 + 1 + -2m = 7 + 1 Combine like terms: -1 + 1 = 0 0 + -2m = 7 + 1 -2m = 7 + 1 Combine like terms: 7 + 1 = 8 -2m = 8 Divide each side by '-2'. m = -4 Simplifying m = -4
| 2x^2=35-3x | | 2B+10=12-B | | 8x-5-(10x-7)= | | 3y=9x+30 | | 52+(3x+2)=90 | | 2xsquared=400 | | z/3=-5 | | 12x^13-12x^2-24x=0 | | g(x)=2x^2+6x-1 | | h=2t^2+12t+10 | | 4x-9y=1 | | 5x+5x-5=45 | | 4x^2+6x^2= | | (5x+20)+(x)=180 | | 4/5=0.2 | | 35xy/40x | | S-11.5=13.5 | | 14+5x(119-7)= | | -3p/51p | | 8y=-6+4 | | m^2-4m=4 | | 6+7x+5x=-78 | | 14+5x(129-7)= | | 2(x+1)=y-1 | | (6+6i)+(3-5i)= | | r^2+121=0 | | -x+5x+9=33 | | 9x+18=90 | | x^3-7x^2+5x+35=0 | | 15+c=17.50 | | 2+45(14)= | | 33=-x+5X+9 |